The Distribution of the Secreted and Intracellular Forms of Plasminogen Activator Inhibitor 2 (PAI-2) in Human Peripheral Blood Monocytes Is Modulated by Serum - Ritchie, Helen; Booth, Nuala A. (Thrombosis and Haemostasis, 1998)
Plasminogen activator inhibitor 2 (PAI-2) is produced by activated monocytes in two forms, intracellular and secreted. We have studied the distribution of these two forms in unstimulated human peripheral blood monocytes and after stimulation by thrombin. Fetal calf serum (FCS) in the culture medium was absolutely necessary for accumulation of intracellular PAI-2; but not for synthesis and secretion. Even at a concentration as low as 0.1%, FCS restored accumulation of intra-cellular PAI-2. Increasing concentrations of FCS resulted in an increase in the ratio of intracellular to secreted PAI-2. The factor that promoted accumulation of intracellular PAI-2 was not a platelet product. Failure of monocytes to accumulate PAI-2 did not reflect leakage due to cell death, as assessed by LDH in culture supernatants. We propose that accumulation of intracellular PAI-2 is not simply due to poor secretion, but is an active process that is modulated by factor(s) found in serum.